Factors Influencing The Disclosure Of Islamic Social Reporting In Islamic Commercial Banks - Euis Sahara; Ibram Pinondang Dalimunthe (JPS (Jurnal Perbankan Syariah), 2023)
This study aims to analyze and show the effect of return on equity (ROE), financing to deposit ratio (FDR), company size, size of the Islamic supervisory board (ISB), and company age on the disclosure of Islamic social reporting (ISR) in Islamic commercial banks (ICB) in the period 2018-2020. This quantitative study uses secondary data, namely annual reports of ICB. The population of this study is ICB registered with the financial services authority (FSA) in 2018-2020, totalling 14 ICB. The sampling technique uses a purposive sampling method so that 12 samples. Data analysis technique using multiple linear regression method with panel data. The results show that ROE, FDR, company size and age significantly affect ISR disclosure. Meanwhile, the size of the Islamic supervisory board does not affect ISR disclosure. Simultaneously ROE, FDR, firm size, size of the Sharia supervisory board, and firm age significantly affect ISR disclosure. This research can complement the existing theory and can be a reference for ICB management to improve the disclosure of social responsibility for the better.